Comparative study between conventional extra capsular cataract extraction versus manual small incision cataract surgery - Laxmiprasad, Gannaram; Shori, Chhaya; Shori, Rakesh; Alli, Ashalatha (International Journal of Research in Medical Sciences, 2017)
Background: Recent reports indicate that both manual small incision cataract surgery and extra capsular cataract excision surgery with posterior chamber intraocular lens implantation are safe and effective for treatment of cataract surgery, however, manual small incision cataract surgery gives better uncorrected vision. Objectives of the study were to compare intraoperative and postoperative complications, to compare induced astigmatism and to compare the visual rehabilitation. Methods: This is a prospective study of 100 consecutive patients assigned to undergo conventional extra capsular cataract excision surgery (50 cases) and manual small incision cataract surgery (50 cases). Study was done for a period of two years at a tertiary care referral hospital. Institutional Ethics Committee permission was taken. Also the informed consent was obtained from each patient. Results: In conventional ECCE, the most common surgically induced astigmatism was WTR in 73.4% of cases with mean of 2.79 D±1.3 on first day. 70% of cases with mean 2.1 D±1.28 and 64% of cases with mean of 1.86 D±1.14 at six weeks. ATR was common in MSICS group, 83.67% of cases with mean of 1.5 D±0.72 on first day, 86% of cases with mean of 1.03 D±0.6 at one week and 88% of cases with mean of 1.27 D±0.81 at six weeks. The induced astigmatism was less in MSICS group compared to ECCE group at first day but after six weeks there was no much significant difference found. Early visual recovery was better in MSICS group Conclusions: MSICS has definitive advantages over conventional ECCE in terms of early visual rehabilitation, minimal surgically induced astigmatism; no suture related complications and reduced surgical time.